Blake saved ![\bold{\$ 433.80}](https://tex.z-dn.net/?f=%5Cbold%7B%5C%24%20433.80%7D)
Option - A
<u>SOLUTION:
</u>
Given, Blake and James are planning to go on a trip.
Blake already has some money saved.
Let the amount saved by Blake be
.
She earns
more by working overtime.
Then, total amount by Blake ![=\$(n+96)](https://tex.z-dn.net/?f=%3D%5C%24%28n%2B96%29)
James has
more than 4 times the amount of money that Blake has saved.
Then, total amount by James will be ![\$ 53+4 \times \$ n=\$(4 n+53)](https://tex.z-dn.net/?f=%5C%24%2053%2B4%20%5Ctimes%20%5C%24%20n%3D%5C%24%284%20n%2B53%29)
If they have
in all, we have to find how much money had Blake originally saved
Now, total amount = ![\$2318](https://tex.z-dn.net/?f=%5C%242318)
![\begin{array}{l}{\rightarrow \text { Amount by Blake }+\text { amount by James }=2318} \\\\ {\rightarrow \mathrm{n}+96+4 \mathrm{n}+53=2318 \rightarrow 5 \mathrm{n}+149=2318 \rightarrow 5 \mathrm{n}=2318-149 \rightarrow 5 \mathrm{n}=2169 \rightarrow \mathrm{n}=433.8}\end{array}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7Bl%7D%7B%5Crightarrow%20%5Ctext%20%7B%20Amount%20by%20Blake%20%7D%2B%5Ctext%20%7B%20amount%20by%20James%20%7D%3D2318%7D%20%5C%5C%5C%5C%20%7B%5Crightarrow%20%5Cmathrm%7Bn%7D%2B96%2B4%20%5Cmathrm%7Bn%7D%2B53%3D2318%20%5Crightarrow%205%20%5Cmathrm%7Bn%7D%2B149%3D2318%20%5Crightarrow%205%20%5Cmathrm%7Bn%7D%3D2318-149%20%5Crightarrow%205%20%5Cmathrm%7Bn%7D%3D2169%20%5Crightarrow%20%5Cmathrm%7Bn%7D%3D433.8%7D%5Cend%7Barray%7D)
Answer:
B) -125a^11
Step-by-step explanation:
(-5a^2)^3·a^5 = (-5)^3·a^6·a^5
= (-5)^3·a^(2·3)·a^5
= (-5)^3·a^6·a^5
= -125·a^(6+5)
= -125·a^11 . . . . matches choice B
_____
The applicable rules of exponents are ...
(a^b)(a^c) = a^(b+c)
(a^b)^c = a^(bc)
We have:
![cot(-x)cos(-x)+sin(-x)=-\frac{1}{f(x)}](https://tex.z-dn.net/?f=cot%28-x%29cos%28-x%29%2Bsin%28-x%29%3D-%5Cfrac%7B1%7D%7Bf%28x%29%7D)
Then we use trigonometric identities to change the negative sign of the trigonometric functions, so:
![-sin(x)-cot(x)cos(x)=-\frac{1}{f(x)}](https://tex.z-dn.net/?f=-sin%28x%29-cot%28x%29cos%28x%29%3D-%5Cfrac%7B1%7D%7Bf%28x%29%7D)
We clear f(x):
![f(x)=\frac{1}{sin(x)+cot(x)cos(x)}=\frac{1}{sin(x)+\frac{cos(x)}{sin(x)}cos(x)}=\frac{1}{sin(x)+\frac{cos^2(x)}{sin(x)}}](https://tex.z-dn.net/?f=f%28x%29%3D%5Cfrac%7B1%7D%7Bsin%28x%29%2Bcot%28x%29cos%28x%29%7D%3D%5Cfrac%7B1%7D%7Bsin%28x%29%2B%5Cfrac%7Bcos%28x%29%7D%7Bsin%28x%29%7Dcos%28x%29%7D%3D%5Cfrac%7B1%7D%7Bsin%28x%29%2B%5Cfrac%7Bcos%5E2%28x%29%7D%7Bsin%28x%29%7D%7D)
we simply what we can:
![f(x)=\frac{1}{\frac{sin^2(x)+cos^2(x)}{sin(x)}}=sin(x)](https://tex.z-dn.net/?f=f%28x%29%3D%5Cfrac%7B1%7D%7B%5Cfrac%7Bsin%5E2%28x%29%2Bcos%5E2%28x%29%7D%7Bsin%28x%29%7D%7D%3Dsin%28x%29)
Thus, the correct answer is;
Answer:
m∠BAC = 105°
m∠FAB = 75°
Step-by-step explanation:
By using the property of an exterior angle of a triangle,
Measure of an exterior angle is equal to the sum of opposite two angles of a triangle.
From the triangle given in the picture,
m∠ABC + m∠BCA + m∠CAB = 180°
(13x - 3)° = (3x + 2)° + 55°
13x - 3 = 3x + 57
13x - 3x = 57 + 3
10x = 60
x = 6
m∠FAB = (13x - 3)° = 75°
m∠ABC = (3x + 2)° = 20°
Since, ∠BAC and ∠FAB are the linear pair of angles,
m∠BAC + m∠FAB = 180°
m∠BAC + 75° = 180°
m∠BAC = 180° - 75° = 105°
Answer:
Answer:
x = 2
Step-by-step explanation:
The vertex form of the parabola is given by
Comparing this equation with vertex form of a parabola , where (h,k) is the vertex
h = 2
k = 3
Hence, vertex is (2,3)
Now, axis of symmetry of a parabola passes through the vertex and divide the parabola in two equal halves.
Hence, axis of symmetry of the parabola is given by
x = h
x = 2
Third option is correct.